1992
DOI: 10.1128/iai.60.12.4984-4988.1992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pasteurella multocida toxin on bone resorption in vitro

Abstract: Pasteurella multocida toxin (PMT), which is the primary etiologic factor in the pathogenesis of progressive atrophic rhinitis in pigs, was found to stimulate bone resorption in vitro. This stimulation was observed both in cultures of murine calvaria by measuring the release of calcium and of the lysosomal enzyme 13-glucuronidase and in murine long bone cultures by measuring the release of calcium. Both systems showed the same dose response curve, with the maximal effect at a concentration of 5 ng/ml. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Thus this protein is as active a mediator of bone resorption as the most potent osteolytic cytokine, IL-1 (116,125). PMT-induced bone resorption was completely inhibited by calcitonin, a circulating hormone able to inhibit osteoclast function, and inhibitors of cyclo-oxygenase partially inhibited this bone resorption (17). While Pasteurella multocida infections in pigs are associated only with nasal turbinate atrophy, it appears from this and in vivo data that PMT can act on bones other than the nasal bones.…”
Section: Fig 3 the Possible Points Of Interaction Between Osteolytimentioning
confidence: 75%
See 2 more Smart Citations
“…Thus this protein is as active a mediator of bone resorption as the most potent osteolytic cytokine, IL-1 (116,125). PMT-induced bone resorption was completely inhibited by calcitonin, a circulating hormone able to inhibit osteoclast function, and inhibitors of cyclo-oxygenase partially inhibited this bone resorption (17). While Pasteurella multocida infections in pigs are associated only with nasal turbinate atrophy, it appears from this and in vivo data that PMT can act on bones other than the nasal bones.…”
Section: Fig 3 the Possible Points Of Interaction Between Osteolytimentioning
confidence: 75%
“…These bones have a different embryonic derivation and often respond differently to the same osteolytic mediator (e.g., TNF or epidermal growth factor, etc.). However, in both assays, PMT produced maximal bone resorption at the extremely low concentration of 5 ng/ml (approximately 30 pM [17]). We have shown that recombinant PMT stimulates significant murine calvarial bone resorption at concentrations as low as 0.1 ng/ml (Ͻ1 pM [76b]).…”
Section: Fig 3 the Possible Points Of Interaction Between Osteolytimentioning
confidence: 94%
See 1 more Smart Citation
“…Calvarium culture. Culture conditions similar to those described previously (7) were used. Briefly, calvarium explants from 4-to 5-day-old ddy mice, bred in our breeding facilities, were obtained aseptically.…”
Section: Methodsmentioning
confidence: 99%
“…PGE2 increases cartilage growth by stimulating chondrocyte proliferation and bone resorption by stimulating osteoclast proliferation (O'Keefe et al, 1992). Evidence for direct cytokine action on bone consists of a Pasteurella multocida induced bone resorption in vitro (Felix et al, 1992) and…”
Section: Bone Growth and Resorptionmentioning
confidence: 99%